Revision of Collema Weber Ex. F.H. Wigg. Genus of Turkiye - Ayhan Turan; Atila Yildiz (EQA)
Many lichens flora studies have been carried out within the borders of Türkiye, and as a result of these studies, a  total of 35 taxa, including 25 species, 9 varieties and 1 subspecies, belonging to the genus Collema, have been  identified. As a result of the studies, the categories of 28 taxa have been changed and they have been transferred  to other genera. As a result of our work, samples were collected from 200 stations. Collema taxa were found in 54  of these stations. Taxa belonging to the genus Collema are C. nigrescens, C. furfuraceum from 12 locations, C.  subnigrescens from 10 locations, C. subflaccidum from 7 locations, C. flaccidum from 5 locations, C. ryssoleum from 3  locations, and C. texanum var. texanum from 1 location collected. When taxa transferred from Collema to other  genera are taken into consideration, the 4 most common taxa are Lathagrium cristatum (90), Enchlium tenax (75),  Blantholla crispa (72) and L. auriforme (50).